Consumo de linaza molida para la reducción de peso corporal en personas con exceso de peso (2011)
ABSTRACT: To describe changes in weight, body fat mass and food intake in overweight and obese people, who consumed 30g of ground flaxseed daily during eight weeks and to report the tolerance to this treatment. Materials and methods: It was an intervention study. A group of 10 overweight adults were selected to voluntarily consume 30g of ground flaxseed through eight weeks. They were asked not to change their usual food intake and their physical activity routine during the intervention. Food consumption, physical activity and anthropometric variables were measured at baseline, week four and week eight. Subject’s tolerance to consumption of ground flaxseed was measured each week. Results: No significant changes in weight (p=0,610), and body fat mass (p=0,866) were observed. Participants did not report adverse effects. Conclusions: Intake of 30 g of ground flaxseed daily for eight weeks, without reductions of caloric intake and without increases in physical activity didn’t show significant weight reductions in overweight individuals.